Validitas Buku Ajar Berbasis Inkuiri Berorientasi Sustainable Society dalam Pengelolaan Sampah pada Materi Pencemaran - Hilda Ernani; Dewi Seprianingsih (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
The purpose of this study is to determine the validity of inquiry-based teaching materials oriented towards sustainable society in waste management on pollution materials. The development model used in this research is 4D, which is modified into 3D with detailed stages, namely: 1) define; 2) design / design; and 3) develop. The research sample was 25 students of the Biology Education Study Program, FKIP, Cordova University. The research instrument used is a validation sheet, which includes a construct and content validation sheet. Data collection techniques in this study by means of validation. The data analysis technique is descriptive quantitative. The results showed that, based on the two expert validators in the construct section which were stated to be very valid, the average score was 3.75 and the percentage was 93.75 with very good criteria. The validation in the content section is stated to be very valid, the average score obtained is 62.5 and the percentage is 91.9 with very good criteria. Based on the results of the validation, it can be concluded that, inquiry-based textbooks oriented towards sustainable society in waste management on the pollution material produced are declared eligible to be used as teaching materials.